Successes and challenges of an online based nutrition awareness program in 9–11-year-old children in four Arab countries: The Ajyal Salima digital platform qualitative study - Carla Habib-Mourad; Carla Maliha; Amira Kassis; Diala Tailfeathers; Marco Bardus; Eman Haji; Lina AlTarazi; Suzan Totah; Nahla Hwalla (PLoS ONE, 2026)
Introduction The rapid expansion of digital technologies has significantly influenced the lives of children and youth, leading many to seek nutrition education through digital platforms. This study aims to assess the usability and acceptability of Ajyal Salima, a nutrition awareness digital platform targeting children aged 9–11, in four Arab countries. Methods A qualitative study was led across four countries: Lebanon, Bahrain, Palestine, and Jordan. Semi-structured focus groups discussions (FGDs) were held separately with children (21 FGDs; n = 145) and parents (16 FGDs; n = 98), complemented by In Depth Interview (IDIs) with teachers (n = 19) and Key Informant Interviews (KIIs) with program staff (n = 8). All interviews and focus groups lasted approximately 40 minutes. Data was analyzed thematically using NVivo software, resulting in four main themes. Results Four major themes emerged: platform’s usability, content enjoyment, changes in children’s habits and recommendations to improve the platform. Overall, parents and teachers found the digital experience positive and useful and the content appropriate for children, particularly younger age groups. Challenges included registration difficulties, technical problems, internet accessibility, low parental involvement, and difficulties integrating the platform into teachers’ schedules. The platform’s animations were less effective in sustaining children’s attention amid evolving digital standards. Conclusion To enhance the platform’s effectiveness, recommendations include simplifying the registration process, enhancing content interactivity, aligning the platform with school curricula, and equipping teachers with supportive resources. Fostering stronger school-family partnerships and engaging parents through community initiatives may be considered to maximize the platform’s potential to promote healthier eating habits and improve nutritional awareness among children and their families, across the region.